2015
DOI: 10.1021/acs.nanolett.5b02811
|View full text |Cite
|
Sign up to set email alerts
|

Organic Monolayer Protected Topological Surface State

Abstract: Perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA)/Bi2Se3 and Fe/PTCDA/Bi2Se3 heterointerfaces are investigated using scanning tunneling microscopy and spectroscopy. The close-packed self-assembled PTCDA monolayer possesses big molecular band gap and weak molecule-substrate interactions, which leaves the Bi2Se3 topological surface state intact under PTCDA. Formation of Fe-PTCDA hybrids removes interactions between the Fe dopant and the Bi2Se3 surface, such as doping effects and Coulomb scattering. Our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…The Drude conductance retains a similar scattering rate, which indicates the organic thin film layers are homogenous and induce no extra impurity scattering. This is consistent with previous spectroscopy studies, which showed that the surface states dispersion is robust to adsorbed molecules [57][58][59][60]. Nevertheless, in contrast to these works that increased the chemical potential by depositing organics [57][58][59][60], we lower it towards the Dirac point.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The Drude conductance retains a similar scattering rate, which indicates the organic thin film layers are homogenous and induce no extra impurity scattering. This is consistent with previous spectroscopy studies, which showed that the surface states dispersion is robust to adsorbed molecules [57][58][59][60]. Nevertheless, in contrast to these works that increased the chemical potential by depositing organics [57][58][59][60], we lower it towards the Dirac point.…”
supporting
confidence: 93%
“…This is consistent with previous spectroscopy studies, which showed that the surface states dispersion is robust to adsorbed molecules [57][58][59][60]. Nevertheless, in contrast to these works that increased the chemical potential by depositing organics [57][58][59][60], we lower it towards the Dirac point. Samples were kept in a desiccator with reduced moisture for the next four months and then re-measured by the THz spectrometer.…”
supporting
confidence: 93%
“…Such a self-assembled PTCDA layer can also be used as a buffer layer to protect the topological surface states (TSSs) of Bi2Se3, which exhibits a Dirac cone-like dispersion similar to G [69]. …”
Section: Ptcda On Layered Substratesmentioning
confidence: 99%
“…The creation of hybrid molecule‐TI interfaces has several advantages, namely (i) the electric field‐driven ionization process can change the molecules charge state only by integer numbers, i.e., by adding or removing single electrons. This results, because of the high degree of charge localization typical of molecules, in a well‐defined sequence of discrete states generated by strong Coulomb repulsions, (ii) molecules can be placed onto TI surfaces without perturbing their topological states by scattering, (iii) contrary to conventional doping, i.e., adatoms, the hybridization of molecules with topological surfaces is reduced, thus preserving their functionality, and (iv) their distribution can be precisely controlled through self‐assembly processes …”
mentioning
confidence: 99%
“…More recently, it has been demonstrated that all these limitations can be overcome at once by using molecules as building blocks [14][15][16][17][18][19]. Molecules have already been successfully used in the past to create hybrid heterostructures with functionalities going beyond those of their constituents [20,21].…”
mentioning
confidence: 99%